2014
DOI: 10.1007/s11105-014-0753-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Scale Transcriptomic Insights into Molecular Aspects of Abiotic Stress Responses in Chickpea

Abstract: Chickpea is an important legume crop plant and various abiotic stresses are the major constraints affecting its overall productivity. For discovery of candidate genes involved in abiotic stress responses, we employed RNA sequencing for transcriptome profiling of roots and shoots of chickpea seedlings subjected to desiccation, salinity, and cold stresses. In total, we generated more than 250 million highquality reads from non-stressed and stressed tissue samples. Data analyses provided a comprehensive view of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 67 publications
3
60
0
Order By: Relevance
“…In the current dataset, significant number of TFs were identified to be differentially expressed. It has been previously reported that TFs of various gene families perform a crucial function in growth and development via gene regulatory networks (Garg, Bhattacharjee, & Jain, ; Shinozaki & Yamaguchi‐Shinozaki, ). The members of several well‐known TF families implicated in growth and development such as bZIP, GRF, and MYB were significantly differentially expressed suggesting an important role of plant TFs in growth and development of the plant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current dataset, significant number of TFs were identified to be differentially expressed. It has been previously reported that TFs of various gene families perform a crucial function in growth and development via gene regulatory networks (Garg, Bhattacharjee, & Jain, ; Shinozaki & Yamaguchi‐Shinozaki, ). The members of several well‐known TF families implicated in growth and development such as bZIP, GRF, and MYB were significantly differentially expressed suggesting an important role of plant TFs in growth and development of the plant.…”
Section: Discussionmentioning
confidence: 99%
“…In the current dataset, significant number of TFs were identified to be differentially expressed. It has been previously reported that TFs of various gene families perform a crucial function in growth and development via gene regulatory networks (Garg, Bhattacharjee, & Jain, 2015;Shinozaki & Yamaguchi-Shinozaki, 2007 (Miyashita & Good, 2008). Cysteine and methionine metabolism regulates plant growth and development and are also involved in seed development process.…”
Section: Validation Of Candidate Genes Identified From Drought Tolementioning
confidence: 99%
“…Tissue specific transcriptomes of chickpea for various tissues and stresses such as leaf (SRX048833), root (SRX048832), flower bud (SRX048834), pod (SRX048835), seed (SRX125162) and nodule (PRJNA214031) were downloaded from SRA (Sequence Read Archive. Stress-specific (salt, desiccation and cold) transcriptome of chickpea root and shoot were retrieved from the SRA database (SRP034839) (Garg et al, 2015). Reads were filtered, trimmed and mapped on the chickpea (desi) genome using TopHat2 (Kim et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Short reads for chickpea root and shoot tissue under three stress conditions- desiccation, salinity and cold, were retrieved from SRA database available under accession number SRP034839 [65]. The reads were mapped onto the predicted gene models in kabuli chickpea genome [23] using BWA-MEM [66] for 454 reads and BWA [67] for Illumina reads.…”
Section: Methodsmentioning
confidence: 99%